COMPUGIRLS' Standpoint: Culturally Responsive Computing and Its Effect on Girls of Color. (September 2013) - Scott, Kimberly A.; White, Mary Aleta
This article investigates the motivations of African American and Latino girls ( N = 41) who navigate urban Southwest school districts during the day, but voluntarily attend a 2-year, culturally responsive multimedia program after school and into the summer. Understanding that girls from economically disadvantaged settings are indeed motivated to become technological innovators but often do not have access to the necessary resources to follow their interest, our program—entitled COMPUGIRLS—assumes a culturally responsive computing approach. This research examines particular features of the program (e.g., asset building, reflections, and connectedness) that attracted and retained the Latina (74%) and African American (19%) adolescent (ages 13-18) participants as well as to what extent the culturally relevant aspects of the curriculum assist with program retention and/or affect the students' vision of themselves as a future technologist. An evaluative approach gathered 2 years of data from the participants. Field notes from observations and interviews were transcribed and reviewed to extract themes and areas of convergence. As a standpoint theory project, the authors center the girls' voices as the primary data sources. Two primary themes emerged from the data to explain girls' sustained motivation. The first was the challenge of learning and mastering the technology. For many, this also included disproving the stereotypes of their abilities by age, gender, and race. The second theme was being able to manipulate technology and learning experiences as a means of self-expression and research, particularly if the results could be used to inform their community and peers. The authors posit that much of the program impact was because of the culturally responsive practices (asset building, reflection, and connectedness) embedded within the curriculum. Implications for urban educators and program developers are considered.